Miniatured Fabry-Perot strain probe based on anti-resonant hollow core fiber. (15th November 2022) - Zhao, Xiaonan; Wu, Xuqiang; Zuo, Cheng; Mu, Shengquan; Zhang, Wujun; Shi, Jinhui; Gui, Lei; Guang, Dong; Yu, Benli
Highlights: We propose a novel miniature Fabry-Perot strain probe based on anti-resonant hollow core fiber. This is the first time that an anti-resonant fiber mentioned in the manuscript has been used to make a Fabry-Perot probe. The designed Fabry-Perot strain probe has no temperature and refractive index crosstalk problems, and can work in a high temperature (up to 1000℃) and humid environment. Different from the previous transmission fiber probe, the reflective strain sensor has a smaller structure. The unique structure of the ARHCF used distinguishes it from other hollow-core fibers by eliminating the need to spend a lot of time on parameter optimization during fiber fusion, resulting in excellent reflection spectra even when the fusion point is severely distorted. Abstract: A novel miniature Fabry-Perot strain probe based on anti-resonant hollow core fiber (ARHCF) is proposed and experimentally demonstrated, which is fabricated by sandwiching a ARHCF between a single-mode fiber (SMF) and a multi-mode fiber (MMF). Two fusion points of the three optical fibers have been worked as mirrors to form a Fabry-Perot interferometer (FPI). The experimental results agree well with the simulation results. The ARHCF differs from the previous hollow core fiber (HCF) by obtaining high-resolution reflection spectra even when the air hole collapses during fiber fusion. By taking advantage of the insensitivity of ARCHF to temperature and refractive index (RI), the FPI is made small enough to work in tight spaces with high temperature (up to 1000 ℃) and humidity, which is unmatched by some previous transmissive strain sensors that are subject to multiparameter cross-sensitivity. This sensor provides new strategies and ideas for the development of strain sensors.